Health-Related Quality of Life and Parental Stress in Children With Fecal Incontinence: A Normative Comparison. Issue 6 (December 2016) - Cushing, Christopher C.; Martinez-Leo, Bruno; Bischoff, Andrea; Hall, Jennifer; Helmrath, Michael; Dickie, Belinda H.; Levitt, Marc A.; Peña, Alberto; Zeller, Meg H.; Frischer, Jason S.
ABSTRACT: Objective: The aim of the present study was to describe the quality of life and parenting stress associated with a child with fecal incontinence (FI). Methods: Female caregivers (n = 170) of children of 3 to 12 years age with FI completed a broad and general measure of quality of life and a measure of parenting stress. Results were compared with proxy reports for a normative sample of healthy children. Results: Caregivers of children with FI reported significantly impaired quality of life for their children and increased parenting stress in all of the respective domains relative to healthy controls. Impairments reported by caregivers were large in magnitude. Similarly, rates of parenting stress were at or greater than the 98th percentile for caregivers of children with FI. Conclusions: Children with fecal incontinence and their families are in need of interventions targeting their quality of life and the stress associated with caregiving. FI appears to be particularly stressful for caregivers who may be in need of support beyond medical management of their child's bowel. Moreover, additional refinements in disease-specific quality of life assessment are needed in this population. Such refinement would allow for more precise measurement of the quality of life processes that are unique to FI. Abstract : Supplemental Digital Content is available in the text